2011
DOI: 10.1371/journal.pone.0028180
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of the Dynamics of Vaginal Microflora during Two Consecutive Menstrual Cycles

Abstract: BackgroundAlthough the vaginal microflora (VMF) has been well studied, information on the fluctuation of the different bacterial species throughout the menstrual cycle and the information on events preceding the presence of disturbed VMF is still very limited. Documenting the dynamics of the VMF during the menstrual cycle might provide better insights. In this study, we assessed the presence of different Lactobacillus species in relation to the BV associated species during the menstrual cycle, assessed the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 55 publications
(77 reference statements)
7
52
0
3
Order By: Relevance
“…Similarly, several longitudinal VMB studies showed that a majority of women have a stable VMB microbiome [23], [26], [54], [59], [62]. A study in post-menopausal women showed that the VMB is usually stable in that group as well [49].…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Similarly, several longitudinal VMB studies showed that a majority of women have a stable VMB microbiome [23], [26], [54], [59], [62]. A study in post-menopausal women showed that the VMB is usually stable in that group as well [49].…”
Section: Resultsmentioning
confidence: 91%
“…Studies also consistently suggest that menses is the largest disturbing factor during the menstrual cycle, with sometimes large reductions in lactobacilli [38], [59], [62], [63], shifts from L. crispatus to L. iners [38], [70], or the appearance of BV-associated bacteria, streptococci or other Gram-positive cocci [54], [70]. Pregnancy, which is also accompanied by high estradiol levels, is associated with high levels of lactobacilli, particularly L. crispatus , and low bacterial diversity [55], [68].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The present study builds upon previous work of our group, where we reported the results of Gram stain and culture for 17 menarchal women, who self-swabbed the vagina daily during two MCs [10]. Here, we add concentrations obtained by quantative PCR for five vaginal key species, i.e.…”
Section: Introductionmentioning
confidence: 94%
“…Fecal samples were shown to harbor only a few clones identified as Actinomyces, with "A. viscosus" and A. odontolyticus being represented (42). Actinomyces species found in the human (female) urogenital tract in the absence of actinomycetal infection include A. meyeri, A. neuii, A. radingae, A. turicensis, and A. urogenitalis (43)(44)(45)(46)(47). After the detection of Actinobaculum schaalii (currently Actinotignum schaalii), a taxon closely related to the members of the genus Actinomyces, in urine, groin swabs, and vaginal swabs (18), it was recently suggested that this organism might be a relatively frequent commensal residing on the skin and mucosae of urogenital sites, but not in the colon, since no detection from feces was made (48).…”
Section: Other Sites Of Bacterial Colonizationmentioning
confidence: 99%